Measuring Islamic Banking Performance Using Maqashid Shariah Index and RGEC: The Malaysian and Indonesian Islamic Banking - Ahmad Agus Hidayat; Elissa Qathrunnada; Andriani Samsuri (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2023)
Islamic banking in Malaysia and Indonesia ranks first (Malaysia) and third (Indonesia) based on the top Islamic financial development indicator (IFDI) countries. However, this great potential has not been matched by a comprehensive performance measurement covering social and sharia aspects as well as the health of Islamic banks. Therefore, this study aims to measure the performance of Islamic banks through the Maqashid Syariah Index and RGEC approaches using quantitative methods. The results showed that through the MSI approach, Malaysian Islamic banking is superior to Indonesian Islamic banking in the aspects of justice and benefit. Through the RGEC approach, the NPF, ROA, FDR, and CAR ratios show that Malaysian Islamic banking is superior. The implications of this research can be useful for Islamic banking in developing the right strategy in order to improve sharia and social performance and bank health.